2007
DOI: 10.1007/s10722-007-9208-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of gliadins and SSRs to analyse the genetic variability of the Spanish collection of cultivated diploid wheat (Triticum monococcum L. ssp. monococcum)

Abstract: This work studied the combined use of gliadins and SSRs to analyse inter-and intraaccession variability of the Spanish collection of cultivated einkorn {Triticum monococcum L. ssp. monococcum) maintained at the CRF-INIA. In general, gliadin loci presented higher discrimination power than SSRs, reflecting the high variability of the gliadins. The loci on chromosome 6A were the most polymorphic with similar PIC values for both marker systems, showing that these markers are very useful for genetic variability stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…amphicarpa accessions on the basis of their morphological features is complicated given the wide variation and overlapping of these traits (Tardío 1997). Differences in seed storage proteins, however, have proved to be useful in attempts to separate accessions of faba bean, grass pea, wheat, lentil and buckwheat (Pascualini et al 1991;Przybylska et al 2000;Ruiz et al 2007;Routray et al 2007;Scippa et al 2008;Li et al 2008). In contrast to the results of Haider and El-Shanshoury (2000), the accessions of Vicia sativa subsp.…”
Section: Discussionmentioning
confidence: 99%
“…amphicarpa accessions on the basis of their morphological features is complicated given the wide variation and overlapping of these traits (Tardío 1997). Differences in seed storage proteins, however, have proved to be useful in attempts to separate accessions of faba bean, grass pea, wheat, lentil and buckwheat (Pascualini et al 1991;Przybylska et al 2000;Ruiz et al 2007;Routray et al 2007;Scippa et al 2008;Li et al 2008). In contrast to the results of Haider and El-Shanshoury (2000), the accessions of Vicia sativa subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Some agromorphological traits such as very high hairy leaf, and long and less dense spike were clearly different from the Spanish accessions of cultivated einkorn (Fig. 1b), which had hairless leaf, and shorter and very dense spikes (Ruiz et al, 2007). Agro-morphological data also indicated that the sample was different from other T. boeoticum accessions maintained at the CRF-INIA.…”
Section: Short Communication Collecting a Population Of Triticum Boementioning
confidence: 76%
“…Table 1 shows the agro-morphological data of the accession. The variables were measured according to IBPGR (1985) and Ruiz et al (2007). Some agromorphological traits such as very high hairy leaf, and long and less dense spike were clearly different from the Spanish accessions of cultivated einkorn (Fig.…”
Section: Short Communication Collecting a Population Of Triticum Boementioning
confidence: 99%
“…Zhaocai et al (2006) identified 14 and 19 allele variants, respectively at Gli-A1m and Gli-A2m of 41 T. monococcum accessions. Ruiz et al (2007) noted that Gli-A2m was the most polymorphic and the most useful to distinguish between einkorn varieties.…”
Section: Resultsmentioning
confidence: 99%